INITIAL RETURN: PERBEDAAN SAHAM SYARIAH DAN NON SYARIAH DI PASAR MODAL INDONESIA - Renny Wulandari (Department of Accounting-Faculty of Economic and Business (FEB), 2014)
This research is based on the phenomenon initial public offering, initialreturn. The purpose of this paper is to find empirical evidence about the influence of stockoffering percentage, offer size, profitability, firm size, IPO risk, financial leverage andliquidity, between syari’a stock and non syari’a stock in the Indonesian Stock Exchange.This research use Regression Model and Chow Test to test the hypothesis which hasdeveloped. The result showed variable IPO risk have positive effect on initial return ofsyari’a stock and variable financial leverage and current ratio have positive effect oninitial return of non syrai’a stock. Conclusion of this research showed that there weredifferent factors that influenced initial return between syari’a stock and non syari’a stock.Contibutions for future studies should use other predictor variables and appendobservation years to get much sample for the researchDOI: 10.15408/akt.v7i1.2644